1996
DOI: 10.1103/physrevb.54.14754
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electrical properties of a metallic rough-thin-film system deposited on liquid substrates

Abstract: A rough-thin-film system, deposited on silicone oil drop surfaces by a rf-magnetron sputtering method, has been fabricated and its structure as well as I-V characteristics have been studied. A characteristic surface morphology at the micrometer scale is observed. The anomalous deposition rate, which strongly depends on the nominal film thickness, can be interpreted under the assumption of the second evaporating and the penetrating effects. We find I c ϰR 0 Ϫ␣ , with ␣ϭ0.52Ϯ0.06, where R 0 and I c are the zero … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
53
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 17 publications
1
53
0
Order By: Relevance
“…Based on the fact that liquid surfaces can be used as thin film substrates, 9,10 vapor phase deposition of metals on liquid substrates was studied in a number of recent investigations. The experiment shows that the interaction in the tangent direction between the metallic film and the liquid substrate is very small, compared with the case that thin films on solid or soft polymer substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the fact that liquid surfaces can be used as thin film substrates, 9,10 vapor phase deposition of metals on liquid substrates was studied in a number of recent investigations. The experiment shows that the interaction in the tangent direction between the metallic film and the liquid substrate is very small, compared with the case that thin films on solid or soft polymer substrates.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] The studies show that the formation process of metal films on liquid surfaces generally includes the following stages: growth of atomic compact clusters, aggregation of branched islands, and finally, the formation of continuous films. In addition, the deposited atoms, compact clusters, and branched islands possess large mobility and they can diffuse and rotate on the liquid surfaces freely, 1,2 which indicates that the interaction between the metal film and the liquid substrate in the tangent direction is very small.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, due to the soft and unstable properties of the underlying liquid substrate, the microstructure and surface morphology of the film can usually evolve in a vacuum or atmosphere condition for several hours before the system reaches a stable state with minimum free energy. [1][2][3][4][5][6][7][8][9][10] In this paper, we report the formation mechanism and surface evolution of thin silver films deposited on silicone oil substrates by a DC-magnetron sputtering method. The formation process is found to be quite similar to other metal films on liquid substrates prepared by various techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore it is expected that various characteristic patterns caused by the internal stress relief may appear apparently in these nearly free sustained films. 12 Here we report the spontaneous formation of large spatial ordered stress relief patterns existing in continuous aluminum ͑Al͒ films deposited on silicone oil surfaces. We anticipate that this nearly free sustained metallic film system subjected to the distinctive effect of the underlying liquid layers will provide a test bed not only for the fundamental research on the internal stress in the films, but also for the technological application of various free sustained films on liquid substrates.…”
mentioning
confidence: 97%
“…[12][13][14][15] It is observed that atoms, atomic compact clusters, and branched islands on liquid substrates possess large mobility and they can diffuse, rotate, and aggregate on the liquid surfaces freely. In principle, the phenomena resulted from the internal stress in continuous thin films deposited on liquid surfaces can emerge obviously because of the weak interaction between the films and the liquid substrates.…”
mentioning
confidence: 99%